Bioinspired structural silicone rubber composites with high thermal conductivity based on vertically aligned hybrid filler film. (October 2022) - Song, Jianan; Zhang, Xi; Wang, Jiaqi; Zhang, Kan
Abstract: To improve the capability of thermal management of thermal conductive silicone rubber (SR) composites, a novel strategy to prepare SR composites with vertically aligned graphene/silicon carbide crystal whisker (SiC) hybrid film was proposed inspired by the typical architecture of the annual rings of trees. Frist of all, a SR/graphene-SiC bilayer film was prepared through drying SR solution and aqueous filler dispersion in turn. Then the bilayer film was rolled and subsequently cured to form SR composite. Poly(ethylene glycol) grafted poly(methylhydrosiloxane- co -dimethylsiloxane) was newly synthesized and used to enhance the interfacial interaction between SR and filler film. The bioinspired structural graphene/SiC/SR composite exhibited a very high thermal conductivity of 6.72 W/(m·K). The composite was determined to be an efficient thermal interface material to reduce the working temperature of light emitting diode, clearly showing the excellent thermal management capability of the obtained SR composites. Graphical abstract: Image 1 Highlights: Thermal conductive SR composites with annual ring structure were prepared. Vertically aligned graphene/silicon carbide hybrid film was constructed. PEG- g -PMHS-PDMS was used to enhance the interfacial interaction. Bioinspired structural SR composites have excellent thermal conductivity.